Isolation and identification of ligninolytic bacterium (Bacillus cereus) from buffalo (Bubalus bubalis) rumen and its effects on the fermentation quality, nutrient composition, and bacterial community of rape silage - Zhong, Huimin; Zhou, Jiayan; Wang, Fan; Wu, Wenqing; Xiong, Haiqian; Yin, Huaihui; Li, Xiang (Frontiers in Microbiology, 2023)
Our goal was to isolate and identify a ligninolytic bacterium from the rumen of buffalo (Bubalus bubalis) and investigate its effects as a silage additive for whole plant rape. Three lignin-degradation strains were isolated from the buffalo rumen, with AH7-7 being chosen for further experiments. Strain AH7-7 with acid tolerance and a 51.4% survival rate at pH 4, was identified as Bacillus cereus. It exhibited a lignin-degradation rate of 20.5% after being inoculated in a lignin-degrading medium for 8 days. We divided the rape into four groups according to the various additive compositions to examine the fermentation quality, nutritional value, and bacterial community after ensiling. Group Bc (inoculated with B. cereus AH7-7 3.0×106 CFU g FW-1), group Blac (inoculated with B. cereus AH7-7 1.0×106 CFU g FW-1, L. plantarum 1.0×106 CFU g FW-1, and L. buchneri 1.0×106 CFU g FW-1), group Lac inoculated with L. plantarum 1.5×106 CFU g FW-1 and L. buchneri 1.5×106 CFU g FW-1), and group Ctrl (no additives). After 60 days of fermentation, the application of B. cereus AH7-7 was potent in modulating the fermentation quality of silage, especially when combined with L. plantarum and L. buchneri, as indicated by lower dry matter loss and higher contents of crude protein, water-soluble carbohydrate, and lactic acid. Furthermore, treatments with the B. cereus AH7-7 additive decreased the contents of acid detergent lignin, cellulose, and hemicellulose. The B. cereus AH7-7 additive treatments reduced the bacterial diversity and optimized the bacterial community compositions of silage, with an increase in the relative abundance of beneficial Lactobacillus and a decrease in the relative abundance of undesirable Pantoea and Erwinia. Functional prediction revealed that inoculated with B. cereus AH7-7 could increase the cofactors and vitamins metabolism, amino acid metabolism, translation, replication and repair, and nucleotide metabolism, while decreasing carbohydrate metabolism, membrane transport and energy metabolism. In brief, B. cereus AH7-7 improved the microbial community, fermentation activity, and ultimately the quality of silage. The ensiling with B. cereus AH7-7, L. plantarum, and L. buchneri combination is an effective and practical strategy to improve the fermentation and nutrition preservation of rape silage.